2009
DOI: 10.1097/hco.0b013e32832f0a5b
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): a causal independent risk factor for coronary heart disease?

Abstract: Although there is highly suggestive evidence for a causal relationship between Lp(a) levels and CHD, large well prepared 'Mendelian randomization' studies are needed to fully explore that relationship. The moderate effect of Lp(a) on cardiovascular risk as well as the difficulty in lowering Lp(a) blood levels makes it less useful in the practice of medicine and public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Eprotirome also reduced the concentration of Lp(a), particularly in those with elevated baseline levels. Although the function and regulation of Lp(a) is still unclear, its concentration has repeatedly been identified as an independent risk factor for cardiovascular disease under strong genetic and hormonal control . How hormonal regulation of Lp(a) secretion from the liver is controlled is unknown, but the magnitude of lowering following eprotirome treatment is similar to that seen in response to oestrogen, testosterone, insulin‐like growth factor I or high‐dose nicotinic acid .…”
Section: Discussionmentioning
confidence: 99%
“…Eprotirome also reduced the concentration of Lp(a), particularly in those with elevated baseline levels. Although the function and regulation of Lp(a) is still unclear, its concentration has repeatedly been identified as an independent risk factor for cardiovascular disease under strong genetic and hormonal control . How hormonal regulation of Lp(a) secretion from the liver is controlled is unknown, but the magnitude of lowering following eprotirome treatment is similar to that seen in response to oestrogen, testosterone, insulin‐like growth factor I or high‐dose nicotinic acid .…”
Section: Discussionmentioning
confidence: 99%
“…The European Atherosclerosis Society Consensus Panel recommended screening for elevated Lp(a) in individuals at intermediated or high CVD risk, and a desirable level of below the 80th percentiles (<~50 mg/dl) as a cut-off for global cardiovascular risk was decided on [7]. However, Gudnason and Dube et al suggested that the clinical practice regarding Lp(a) might still be of limited use because of Lp(a)’s moderate effect on CVD risk and unknown functional mechanisms underlying the association [6, 8]. …”
Section: Lp(a) As a Cardiovascular Risk Factor In General Populationsmentioning
confidence: 99%
“…Recent data from large-scale meta-analyses and genetic association studies using Mendelian randomization analyses provide highly suggestive evidence for a potentially causal role of Lp(a) in affecting CVD risk in general populations [2–5], promoting the discussion regarding utility of Lp(a) in clinical practice [68]. Patients with Type 2 diabetes are featured by clustered metabolic abnormalities and an approximately two- to four-fold increased risk of CVD compared with nondiabetics [9, 10].…”
mentioning
confidence: 99%
“…Interestingly, Lp(a) has structural homology to plasminogen and it induces the production of PAI‐1 . A recently published meta‐analysis of 31 prospective studies shows a direct relationship between Lp(a) and CVDs, further supporting the role of this atherogenic lipoprotein as a risk factor for CVDs . Unfortunately, the fact that Lp(a) occurs in nature under different isoforms, together with the relatively limited pharmacological approaches capable to modulate its levels, render this biomarker of little value in the medical practice.…”
Section: Introductionmentioning
confidence: 99%